2009
DOI: 10.1002/pon.1642
|View full text |Cite
|
Sign up to set email alerts
|

Looking past the obvious: experiences of altered masculinity in penile cancer

Abstract: That men should have an altered sense of masculine identity following penile cancer surgery is not unexpected. However, the ways in which altered masculinity manifested itself were both subtle and insidious. The results have implications for clinical practice and demonstrated the need for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 25 publications
(36 reference statements)
5
61
0
4
Order By: Relevance
“…In common with findings from a Welsh study (Bullen et al, 2010) men's narratives of masculinity were interlaced with a hegemonic discourse of stoicism, independence, robustness and resiliency. Some researchers have found that this enactment of 'maleness' is a barrier to the in-depth, nuanced account of experiences that interviews seek (Oliffe and Mróz, 2005).…”
Section: Eliciting Narrativessupporting
confidence: 60%
See 2 more Smart Citations
“…In common with findings from a Welsh study (Bullen et al, 2010) men's narratives of masculinity were interlaced with a hegemonic discourse of stoicism, independence, robustness and resiliency. Some researchers have found that this enactment of 'maleness' is a barrier to the in-depth, nuanced account of experiences that interviews seek (Oliffe and Mróz, 2005).…”
Section: Eliciting Narrativessupporting
confidence: 60%
“…The standard treatment is to surgically remove the primary tumour; the extent of the excision is determined by the size and staging of the cancer (Pizzocaro et al, 2010). Whilst treatment is usually effective, the physical and psychological effects can be profound (Opjordsmoen and FossÅ, 1994), impacting not only on the form and function of the penis (Maddineni et al, 2009, Branney et al, 2011 but also on the self-image and mental well-being of those receiving treatment (Ficarra et al, 2000, Romero et al, 2005, Bullen et al, 2010.…”
Section: Penile Cancer and The Pepc Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The Welsh study that met our inclusion criteria [8][9][10] provides an example of how we could explore quality of life after treatment for penile cancer; one-on-one semi-structured interviews guided by 6-8 questions, which encourage the participant to talk about their experiences. Nevertheless, there are a wide range of qualitative data collection and analytic methods available [21] , which often draw upon unique ways of thinking about and exploring the world.…”
Section: Resultsmentioning
confidence: 99%
“…Only one Welsh study by Bullen et al, reported across three publications [8][9][10] , met our inclusion criteria and therefore a synthesis was impossible. There were 5 borderline studies (across 8 publications [11][12][13][14][15][16][17][18] ) from 4 countries (see Table 1).…”
Section: Search Outcomementioning
confidence: 99%